2013
DOI: 10.1186/1754-9493-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Subjective impact of traumatic brain injury on long-term outcome at a minimum of 10 years after trauma– first results of a survey on 368 patients from a single academic trauma center in Germany

Abstract: BackgroundTraumatic Brain Injury (TBI) may lead to significant impairments in personal, social and professional life. However, knowledge of the influence on long-term outcome after TBI is sparse. We therefore aimed to investigate the subjective effects of TBI on long-term outcome at a minimum of 10 years after trauma in one of the largest study populations in Germany.MethodsThe current investigation represents a retrospective cohort study at a level I trauma center including physical examination or standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The investigation was designed as a retrospective cohort study at a level I trauma center. The clinical database was generated for this study including all patients with TBI at least 10 years after trauma referring to December 1 st 2009 [ 16 ]. Participants have not been involved to other studies.…”
Section: Methodsmentioning
confidence: 99%
“…The investigation was designed as a retrospective cohort study at a level I trauma center. The clinical database was generated for this study including all patients with TBI at least 10 years after trauma referring to December 1 st 2009 [ 16 ]. Participants have not been involved to other studies.…”
Section: Methodsmentioning
confidence: 99%
“…3. Reported mean GOS scores showed rather 'favourable' longterm outcome ranging from 3.8 to 4.4 [3,8,38].…”
Section: Glasgow Outcome Scalementioning
confidence: 98%
“…Follow-up ranged from 2 to 15 years. Follow-up periods up to 5 years were reported in 13 studies (65%) [1,4,7,8,26,38,41,42,57,78,90,92,93], periods from 5 to 10 years in five studies (25%) [36,47,68,73,81], and a follow-up of more than 10 years was reported in two studies (10%) [2,3].…”
Section: Study Characteristics and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations